Electrical characteristics of silicon percolating nanonet-based field effect transistors in the presence of dispersion. (May 2018) - Cazimajou, T.; Legallais, M.; Mouis, M.; Ternon, C.; Salem, B.; Ghibaudo, G.
Highlights: Fabricated NN-FET devices demonstrated overall P-type FET functionality. A LambertW -function based compact model was used to extract electrical parameters. Variation of apparent low-field mobility with geometry and NW density was explained. Impact of NWs threshold voltage dispersion on NN-FET turn-on was modelled. Abstract: We studied the current-voltage characteristics of percolating networks of silicon nanowires (nanonets), operated in back-gated transistor mode, for future use as gas or biosensors. These devices featured P-type field-effect characteristics. It was found that a LambertW function-based compact model could be used for parameter extraction of electrical parameters such as apparent low field mobility, threshold voltage and subthreshold slope ideality factor. Their variation with channel length and nanowire density was related to the change of conduction regime from direct source/drain connection by parallel nanowires to percolating channels. Experimental results could be related in part to an influence of the threshold voltage dispersion of individual nanowires.